Q. 65

Find the

Answer :


Let Tn denotes the nth term of the given series

Tn = [nth term of 1, 2, 3 …..] × [nth term of 2, 3, 4 …..]

    = [1 + (n – 1) 1] [2 + (n – 1) 1]

    = n(n + 1)

Tn = n2 + n

Sn = ∑ n2 + ∑ n

    =

    =

    =
    =
    =
    =

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses